EVALUASI NUTRISI PERBEDAAN RASIO DEDAK PADI DAN AMPAS BIR DITINJAU DARI NILAI TDN RANSUM DOMBA LOKAL JANTAN - Saputro, Thomas; Widyawati, Susi Dwi; Suharto, Suharto (Universitas Sebelas Maret (UNS), 2016)
This study aimed to determine the effect of rice bran (DP) and industrial waste beer or beer dregs (AB) with different ratios on TDN local sheep ration and to know the optimal level of provision. Sheep were used in this study were male local sheep weighing 15 kg ± 1.5 kg as much as 12 heads. Treatment ration consists of forage and concentrates with a ratio of 60%: 40% (in DM) in the form of grass king, DP and AB. The design used in this study is a Completely Randomized Block Design (RCBD) with three treatments and four replications. Treatment applied is P1 = 60% Grass King + 29% DP + 9% AB + 2% Premix, P2 = 60% Grass King + 19% DP + 19% AB + 2% Premix, P3 = 60% Grass King + 9 % DP + 29% AB + 2% Premix. Variables measured are nutrients (crude protein = PK, extract ether = LK, crude fiber = SK and Nitrogen free extract = BETN) can be digested. The results showed that PKdd and LKdd strongly influenced (P <0.01) by the ratio of DP and AB. The use of DP and AB ratio of 19%: 19% and 9% DP AB : 29% highly significant to increase PKdd and LKdd (PK ss: 6.71 vs 7.64; 8.12 and the LKdd: 4:07 vs 4:27; 4:36). While carbohydrates are composed of SKdd and BETNdd did not influenced by differences in the ratio of DP and AB. The use of rice bran and the dregs of beer at local male sheep give the best TDN value at the level of 19% and 19% rice bran and industrial waste beer or beer dregs.